OPTIMALISASI PENYELESAIAN PENGADUAN PUBLIK MELALUI SP4N- LAPOR!: STUDI KASUS DI KABUPATEN LAMPUNG TIMUR - Nida Nabila (Universitas Diponegoro, 2026)
The effectiveness of digital public complaint systems has become a critical issue in strengthening local governance accountability. This study analyzes the optimization of public complaint resolution through SP4N-LAPOR! in East Lampung Regency and identifies inhibiting and supporting factors affecting its implementation. Using a qualitative descriptive approach, data were collected through in-depth interviews and document analysis. The analysis was guided by Gorton’s (2005) seven principles of complaint handling. The findings reveal that complaint resolution has not been fully optimized due to weak inter-agency coordination, limited human resource capacity, and inconsistent institutional commitment. However, regulatory support, leadership engagement, and digital infrastructure availability serve as enabling factors. This study contributes to the discourse on digital governance by emphasizing that technological systems alone are insufficient; institutional capacity and organizational coordination remain decisive determinants of effective complaint resolution.